Bulletin of Rhode Island School of Design - Rowe, L. Earle (Providence-Rhode Island : Rhode Island School of Design, 1913)
The Bulletin of the Rhode Island School of Design began publication with the January 1913 issue for the purpose of spreading “knowledge about the activities of the institution and the advance of art in the state.” The eight page Bulletin, edited by RISD Director L. Earle Rowe (1912-1937), contained short essays by Rowe on works of art held by the Museum of Art, information on exhibits, accessions, and loans, as well as brief notices on the School, the Library, corporate officers, publications, and Museum admissions policies. Over time the Bulletin expanded to 16+ pages as the essays increased in length and number. (Digital Commons)
Online: https://digitalcommons.risd.edu/risdmuseum_publications_bulletinoftherhodeislandschoolofdesign/ (1913-1937)
Engels
Tijdschriften
Keywords: Rhode Island School of Design (Providence-Rhode Island).